SAT0180 Onset of Action of Sarilumab in Patients with Rheumatoid Arthritis in 2 Phase 3 Studies. (15th July 2016) - Fleischmann, R.; Mangan, E.K.; van Adelsberg, J.; Fay, J.; van Hoogstraten, H.; Bauer, D.; Thompson, D.; Kivitz, A.; Burmester, G.R.
Abstract : Background: The investigational human anti–interleukin 6 receptor monoclonal antibody sarilumab plus methotrexate (MTX) has demonstrated efficacy in patients with rheumatoid arthritis (RA) and inadequate response to MTX (MOBILITY; NCT01061736 ), 1 while sarilumab plus conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) demonstrated efficacy in patients with RA and inadequate response or intolerance to tumor necrosis factor (TNF) inhibitors (TARGET; NCT01709578 ). 2 Among the most common treatment-emergent adverse events in both studies were infections, neutropenia, injection site reactions, and increased transaminases. Objectives: This analysis of MOBILITY and TARGET study data assessed the time to onset of clinical efficacy of sarilumab and the durability of response over 24 weeks. Methods: Adults with active, moderate-to-severe RA were randomized to 1 of 3 groups receiving subcutaneous sarilumab 150 or 200 mg or placebo every 2 weeks (q2w) plus background MTX (MOBILITY) or csDMARDs (TARGET). Clinical efficacy was evaluated in these patients at weeks 2, 4, 8, 12, and 24 in a post hoc analysis. ACR20/50/70 response rates were analyzed using the 2-sided Cochran-Mantel-Haenszel test stratified by prior biologic use and region (MOBILITY) or by region and number of prior TNF inhibitors (TARGET); nonresponder imputation was applied for patients who started rescue medication or discontinued the study. Changes from baseline in Health Assessment Questionnaire–Disability Index (HAQ-DI), 28-joint disease activity score by C-reactive protein (DAS28-CRP), and clinical disease activity index (CDAI) were analyzed with a mixed model for repeated measures; no data were imputed. Results: Baseline demographic and disease characteristics were similar between treatment groups in both studies. 1, 2 Improvements in ACR20 responses were observed as early as week 2 in both studies, with nominal P <0.05 observed at week 8 for all sarilumab-treated groups in both studies. Similar trends were observed for ACR50 and ACR70 responses. Greater reductions in DAS28-CRP mean change from baseline vs placebo were observed with both doses of sarilumab by week 2 in both studies (nominal P <0.05). Similarly, numerical improvements in HAQ-DI and CDAI were observed with both doses of sarilumab vs placebo by week 4 in both studies (nominal P <0.05; Table ). Improvements in all efficacy parameters were sustained through the end of each study (ie, week 52 for MOBILITY and week 24 for TARGET). The most common treatment-emergent adverse events at week 12 were infection and neutropenia, consistent with the safety profile previously reported for the entire study periods. Conclusions: Sarilumab rapidly improved signs and symptoms of RA in patients with inadequate response to MTX (MOBILITY) or TNF inhibitors (TARGET), and improvements were sustained through the end of treatment. References: Genovese et al. Arthritis Rheumatol. 2015;67:1424–1437 Fleischmann et al. Presented at: ACR; Nov. 7–11, 2015; San Francisco, CA Acknowledgement: This study was sponsored by Sanofi and Regeneron Pharmaceuticals, Inc. Editorial assistance was provided by Kristi Porter, PhD, MedThink SciCom, and funded by Sanofi and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: R. Fleischmann Grant/research support from: AbbVie, Amgen, Ardea Biosciences, Bristol-Myers Squibb, Celgene, GlaxoSmithKline, Eli Lilly, Pfizer, Roche, Sanofi, and UCB, Consultant for: AbbVie, Akros Pharma, Amgen, AstraZeneca, Bristol-Myers Squibb, Janssen, Eli Lilly, Pfizer, Roche, and UCB, E. Mangan Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, J. van Adelsberg Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, J. Fay Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, H. van Hoogstraten Shareholder of: Sanofi, Employee of: Sanofi, D. Bauer Shareholder of: Sanofi, Employee of: Sanofi, D. Thompson Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, A. Kivitz Shareholder of: Sanofi and Regeneron Pharmaceuticals, Inc., Consultant for: Sanofi, Pfizer, Roche, and UCB, G. Burmester: None declared